Remote monitoring of implantable loop recorders reduces time to diagnosis in patients with unexplained syncope: a multicenter propensity score-matched study - Russo, Vincenzo; Rago, Anna; Grimaldi, Nicola; Chianese, Raffaele; Viggiano, Aniello; D’Alterio, Giuliano; Colonna, Diego; Mattera Iacono, Agostino; Papa, Andrea Antonio; Spadaro Guerra, Andrea; Gargaro, Alessio; Rapacciuolo, Antonio; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: There is little data on remote monitoring (RM) of Implantable Loop Recorders (ILRs) in patients with unexplained syncope and whether it confers enhanced diagnostic power. Objective: To evaluate the effect of RM in ILR recipients for unexplained syncope for early detection of clinically relevant arrhythmias by comparison with a historical cohort with no RM. Methods: SyncRM was propensity score (PS)-matched study prospectively including 133 consecutive patients with unexplained syncope and ILR followed-up by RM (RM-ON group). A historical cohort of 108 consecutive ILR patients with biannual in-hospital follow-up visits was used as control group (RM-OFF group). The primary endpoint was the time to the clinician’s evaluation of clinically relevant arrhythmias (types 1, 2, and 4 of the ISSUE classification). Results: The primary endpoint of arrhythmia evaluation was reached in 38 patients (28.6%) of the RM-ON group after a median time of 46 days (interquartile range, 13-106) and in 22 patients (20.4%) of the RM-OFF group after 92 days (25-368). The PS-matched adjusted ratio of rates of arrhythmia evaluation was 2.53 (95% confidence interval, 1.32-4.86) in the RM-ON versus RM-OFF group (p=0.005). Conclusion: In our PS-matched comparison with a historical cohort, RM of ILR patients with unexplained syncope was associated with a 2.5-fold higher chance of evaluations of clinically relevant arrhythmias as compared with biannual in-office follow-up visits.